(3GdMHGFc aj CNHGQ GdedGFcs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3GdSjO MGaX YKeGf GdTcQi Hf jhSa GdeYQha HhGYX RGOg s)
(3ChdgG (B:s
(3GdMeO ddg LGYd GdedGFcI QSdkG Chdi CLfMI CeG HYO agPG JCdja dWja LeYJg ai CNHGQ GdedGFcI GdCHQGQ ESJhYHJ ajg eG hQOJ Hg GdCMGOjK hGdBKGQ SejJg GdMHGFc ai CNHGQ GdedGFc s
(3BNQgG (B:s
(3GfJgi hGddg CYde hcGf GdaQGZ ef JYdjag ChGFd TgQ ThGd GdPi gh ef SfI EKfi hNeSjf hCda ef GdgLQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdMOjK h GdeUWdMs